Effectiveness of health literacy interventions on anxious and depressive symptomatology in primary health care: A systematic review and meta-analysis - Magallón-Botaya, Rosa; Méndez-López, Fátima; Oliván-Blázquez, Bárbara; Carlos Silva-Aycaguer, Luis; Lerma-Irureta, David; Bartolomé-Moreno, Cruz (Frontiers in Public Health, 2023)
Background Affective disorders are a debilitating and very prevalent problem throughout the world. Often these are associated with the onset of comorbidities or a consequence of chronic diseases. Anxiety and depression are associated with poor social and personal relationships, compromised health. We aimed to synthesize evidence from studies measuring the impact of a health literacy (HL) intervention on the improvement of affective disorders. Methods For this systematic review and meta-analysis, we searched PubMed/MEDLINE, Embase, Web of Science, Ibecs, Cuiden, Scielo, Science Direct and Dialnet for exclusively randomized controlled trial studies (RCTs) published between 1 Jan 2011, and 31 May 2022. The search terms employed were “health literacy,” “health knowledge,” “anxiety,” “anxiety disorder,” “depression,” “depressive disorder,” and “adult.” The risk of bias assessment was performed using the Cochrane Collaboration Revised Risk of Bias tool (RoB2). We conducted random-effects meta-analyses and explored heterogeneity using meta-regression and a stratified survey. Results Of 2,863 citations found through the initial screening, 350 records were screened by the title and abstract for their themes and relevance. Finally, nine studies complied with the inclusion criteria for the meta-analysis. 66.66% of studies (n = 6) were rated as having a low risk of bias and 33.33% (n = 3) were judged to raise some concerns. The health literacy interventions were associated with −1.378 reduction in depression and anxiety questionnaires scores [95% CI (−1.850, −0.906)]. Low mood disorder scores are associated with better mental health and wellbeing. Conclusion Our findings demonstrate that an HL intervention in relation to the symptoms associated with affective disorders improves the emotional state of patients in PHC, with a moderately positive effect in reducing depression and anxiety.